Morphofunctional transformations during the thyroid morphogenesis of the Wistar rats offspring after intrauterine dexamethasone exposure - Fedosieieva, O. V.; Bushman, V. S.; Necheporenko, A. G.; Федосєєва, Олена Станіславівна; Бушман, Вікторія Сергіївна; Нечепоренко, Альона Геннадіївна (My University, 2021)
Background. In recent years, the prevalence of thyroid pathologies of various origins among children in the world has reached a significantly high level. The use of glucocorticoids during pregnancy remains a debatable issue in obstet-rics today, as they can both positively and negatively affect the processes of organ morphogenesis and be the cause of patho-logical conditions in the postnatal period. Objective: to establish the features of morphofunctional transformations during the morphogenesis of the thyroid gland of the offspring of rats at an early age in normal and after intrauterine action of dexame-thasone. Methods. 108 thyroid glands of rats of 3 experimental groups were microscopically examined using histological and immunohistochemical methods, followed by statistical processing of the obtained results. Results. Against the background of high levels of total follicular thyrocytes per 1 day of life in animals that received prenatal dexamethasone, cytoplasmic ex-pression of TgAb was expressed, which correlated with the indicators of nuclear and cytoplasmic Fox-1 expression. From the 7th to the 11th day, a decrease in the total number of thyrocytes per unit area was observed due to the accumulation of colloid in the follicles, an increase in Fox-1 cytoplasmic expression and a decrease in nuclear expression, against the background of increased proliferative activity. By day 21, Fox-1 cytoplasmic and nuclear expression were almost identical. There was a decrease in the intensity of TgAb expression in the cytoplasm of thyrocytes and its expression in the colloid, a decrease in the number of Ki-67 positive thyrocytes per conditional unit area compared with the previous observation period. Conclusion. It was found that prenatal exposure of dexamethasone causes the offspring accelerate the development of morphological struc-tures of the thyroid gland, but functionally they are in a state of stress of both the synthesizing apparatus and the process of hormone excretion, which is expressed in the imbalance of immunohistochemical expression of Fox-1 and TgAb. Such thy-rocytes with signs of disturbances in synthetic activity desquamate into the lumen of the follicles, while on the 11th day we compensatory increase in the proliferative activity of the thyroid epithelium. Актуальність. В останні роки розповсюдженість патологій щитоподібної залози різного ґенезу серед дитячого населення світу сягнула значно високого рівня. Дискусійним питанням в ак-шерстві на сьогодні залишається питання використання глюкокортикоїдів під час вагітності, адже вони можуть як позитивно, так і негативно впливати на процеси морфогенезу органів та бути причиною виникнення патологічних станів у післянатальному періоді. Мета: встановлення особливостей морфофункціональних перетворень в ході морфогенезу щитоподібної залози потомства щурів у ранньому віці в нормі та після внутрішньоутробної дії дексаметазону. Методи. Мікроскопічно досліджено 108 щитоподібних залоз щурів 3 експериментальних груп із застосуванням гістологічних та імуногістохімічних методів, з подальшою статистичною обробкою отриманих результатів. Результати. На тлі високих показників загальної кількості фолікулярних тироцитів на 1 добу життя у тварин, які пренатального отримали дексаметазонб була виражена цитоплазматична експресія TgAb, що корелювало з показниками нуклеарної та цитоплазматичної Fox-1 експресії. З 7-го по 11-й день встановлено зниження загальної кількості тироцитів на умовну одиницю площі за рахунок накопичення колоїду у фолікулах, зростання Fox-1 цитоплазматичної експресії та зниження нуклеарної експресії, на тлі збільшення проліферативної активності. До 21 доби показники Fox-1 цитоплазматичної та нуклеарної експресії були майже тотожними. Відбувалося зменшення інтенсивності експресії TgAb в цитоплазмі тироцитів та вираженость її у колоїді, зменшення кількості Ki-67 позитивних тироцитів на умовну одиницю площі у порівнянні з попереднім строком спостереженням. Підсумок. Встановлено, що пренатальне введення дексаметазону викликає у потомства прискорення розвитку морфологічних структур щитоподібної залози, але функціонально вони знаходяться у стані напруги як синтезуючого апарату так і процесу виведення гормонів, що виражається у дисбалансі імуногістохімічних показників експресії Fox-1 та TgAb. Такі тироцити з ознаками порушень у синтетичній діяльності десквамують у просвіт фолікулів, натомість на 11 добу компенсаторно бачимо зростання проліферативної активності тиреоїдного епітелію.
Mорфофункціональнi перетворення у ході морфогенезу щитоподібної залози потомства щурів лінії Wistar після внутрішньоутробного впливу дексаметазону
Fedosieieva O. V. - 0000-0003-2247-1965; Bushman V. S. - 0000-0002-5833-0155; Necheporenko A. G. - 0000-0003-0981-3641.
Keywords: thyroglobulin; thyroid gland; rats; dexamethasone; parenchymal organs; immunohistochemistry; тироглобулін; щитоподібна залоза; щури; дексаметазон; паренхіматозні органи; імуногістохімія